2019
DOI: 10.1002/joc.6125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extreme temperature and precipitation indices: Using an innovative daily homogenized database in Israel

Abstract: This study examines the 1950–2017 temporal changes in climate extremes in Israel, which is located in the East Mediterranean (EM), a region which suffers from a scarcity of long and reliable datasets. It is well known that most long‐term records are affected by artificial shifts most commonly caused by station relocation, instrumental modification and local environmental changes. Therefore, for the first time, a thorough homogenization (detection and correction) routine was developed and implemented in the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 67 publications
7
55
1
Order By: Relevance
“…Most areas were also characterized by a downward trend in the summer precipitation (Deitch et al, 2017). During this period, reduction in annual and summer precipitations has predominated over the Iberian Peninsula (Río et al, 2011;Rodrigo and Trigo, 2007), Italy (D'Oria et al, 2017), France (Dayon et al, 2018), Greece (Markonis et al, 2017), Croatia (Gajić-Čapka and Cindrić, 2011), Turkey (Çiçek and Duman, 2015), Israel (Yosef et al, 2019), etc. Over the eastern part of the Mediterranean region, trends in precipitation indices consistent with drier conditions were also found, i.e., positive trends in the maximum number of consecutive dry days and negative trends in the annual number of days with precipitation higher than 10 mm (Kostopoulou and Jones, 2005).…”
Section: C4mentioning
confidence: 99%
See 1 more Smart Citation
“…Most areas were also characterized by a downward trend in the summer precipitation (Deitch et al, 2017). During this period, reduction in annual and summer precipitations has predominated over the Iberian Peninsula (Río et al, 2011;Rodrigo and Trigo, 2007), Italy (D'Oria et al, 2017), France (Dayon et al, 2018), Greece (Markonis et al, 2017), Croatia (Gajić-Čapka and Cindrić, 2011), Turkey (Çiçek and Duman, 2015), Israel (Yosef et al, 2019), etc. Over the eastern part of the Mediterranean region, trends in precipitation indices consistent with drier conditions were also found, i.e., positive trends in the maximum number of consecutive dry days and negative trends in the annual number of days with precipitation higher than 10 mm (Kostopoulou and Jones, 2005).…”
Section: C4mentioning
confidence: 99%
“…Increased frequency and intensity of droughts in the Mediterranean region is not just a consequence of natural variability; evidences for anthropogenically forced drying were also determined (Cook et al, 2016), among which key forcings were anthropogenic greenhouse gasses and aerosols, and the sea surface temperatures (Hoerling et al, 2012). Despite a decrease in the total precipitation, studies found an upward tendency in the extreme precipitation over many Mediterranean areas (Abbasnia and Toros, 2019;Nastos and Zerefos, 2008;Ribes et al, 2019;Yosef et al, 2019;etc.). Similar changes in precipitation were observed in the Mediterranean part of Southeast Europe where Montenegro is located.…”
Section: C4mentioning
confidence: 99%
“…techniques are often limited to evaluating changes in the mean rather than extremes (Peña-Angulo et al, 2020;Ribeiro et al, 2016;Yosef et al, 2019).…”
Section: Is the Timing Of Events Changing?mentioning
confidence: 99%
“…The past two decades witnessed a steady increase in the application of the Expert Team on Climate Change Detection and Indices (ETCCDI) recommendations for monitoring climate extremes (including by the Intergovernmental Panel on Climate Change, IPCC; e.g., Frich et al, 2002; Aguilar et al ., 2005; Zhang et al ., 2005a; Alexander et al ., 2006; Klein Tank et al ., 2006; Vincent and Mekis, 2006; Donat et al ., 2013; Yosef et al ., 2019). The ETCCDI defined a total core set of 27 indices based on daily temperature values or daily precipitation amount.…”
Section: Introductionmentioning
confidence: 99%